A systematic review and meta-analysis of the evidence on the acute effects of caffeine on sport-specific skills, physical performance, and physiological function in female basketball players - Zhang, Z.; Yin, M.; Qiu, B.; Meng, F.; Wu, B.; Wang, Y.; Cheng, Z.; Wang, X.; Wang, Y.; Lu, Z.; Sun, Y.; Lai, J. (Frontiers in Nutrition, 2026)
Introduction: Previous original research and meta-analyses have shown that caffeine enhances performance in basketball. However, most studies on caffeine`s effects in basketball have focused on male or mixed-gender samples, and there is currently no meta-analysis specifically on caffeine`s impact on female basketball performance. This study aimed to synthesize current evidence to examine the effects of caffeine supplementation on multidimensional performance outcomes in female basketball players.